A Study on Cash Flow Management in Retail Operations at Haldiram Foods International - Hedau, Shubhangi Govinda; Tekade, Atul (Journal of Neonatal Surgery, 2025)
Effective cash flow management plays a pivotal role in maintaining the financial stability and operational efficiency of retail businesses. Retail operations, especially in large organizations like Haldiram Foods International, face unique challenges in managing cash flow due to fluctuating customer demands, supply chain complexities, and inventory management issues. This study investigates the cash flow management strategies employed by Haldiram Foods International, focusing on their impact on retail operations. The research examines how cash flow forecasting, working capital management, and payment cycle strategies contribute to the financial health of the organization. By analysing internal financial data, interviews with key stakeholders, and observations of day-to-day operations, this study identifies best practices and potential areas for improvement. Key factors such as seasonal sales variations, vendor payment terms, and inventory turnover rates are explored to understand their influence on cash flow. The findings reveal that while Haldiram Foods has robust cash flow management systems in place, certain operational inefficiencies and external market factors occasionally create challenges. The research highlights the need for enhanced technological integration, improved demand forecasting models, and dynamic cash management practices to further streamline operations. By implementing these strategies, retail organizations can ensure better liquidity, reduce financial risks, and improve overall business performance. This study provides valuable insights for retail managers and financial analysts looking to optimize cash flow processes in similar organizations